Industrial training report: National Library of Malaysia / Nur Nabila Mohamad Zainal - Mohamad Zainal, Nur Nabila (Universiti Teknologi MARA, Negeri Sembilan, 2018)
The Industrial Training subject IMC690 provides pre-professional work experience with specific assignments and responsibilities. It is one of the compulsory subjects for students who taking a degree in Bachelor of Information Science (HONS) Library Management (IM244). To fulfil the industrial training requirement, the trainee must undergo at least. five months training at the organization approved by the faculty starting from February 2018 until June 2018. The National Library of Malaysia is an industrial training place chosen because National Library of Malaysia is the parent organization for all libraries in Malaysia and known as the institution that serve users both inside and outside the country. This report consists of five chapters represent introduction, organization information. industrial training activities, industrial training reflection and conclusion. This report is made to clarify what exactly student has done during industrial training. Industrial training program is the best platform to train student on how to adapt themselves with the working environment and being exposed to the real situations in applying the tasks given.